Reconstruction of repeated Quaternary slope failures in the northern South China Sea - Sun, Q; Cartwright, J; Xie, X; Lu, X; Yuan, S; Chen, C (Elsevier, 2018)
A series of Quaternary mass transport deposits (MTDs) with a total areal extent of ~11,000 km2 and a conservative volume estimate of ~1035 km3 are observed in the Pearl River Mouth Basin (PRMB), northern South China Sea (SCS), based on integrated analysis of extensive 2-D/3-D seismic data, multibeam bathymetric data and ODP/IODP wells. Unlike other large MTDs worldwide, the MTDs in this study are not directly sourced from slopes built on major deltaic depositional systems. Moreover, they are remarkable in that the whole PRMB is a giant debris flow corridor that has transected a broad subsided continental margin. The MTDs in this study have a large evacuation zone on the slope and a depositional zone in the ocean basin connected by a narrow pathway. Six events of MTDs (MTDa - MTDd on the slope and MTDo1 - MTDo2 in the ocean basin) have been identified as being separated by basal erosional surfaces defined by strong negative seismic reflections. Similar ages and volumes (depleted volume of MTDb on the slope and the depositional volume of MTDo2) suggest that MTDo1 and MTDo2 correlate with MTDa and MTDb, respectively. The major factor controlling the occurrence of slope failures is argued to be the presence of a key reflection package. This package is interpreted to consist of gas-charged, coarse-grained sediments deposited during a relative lowstand of sea level, overlain by a unit of fine-grained sediments. Other contributing factors that influenced the morphology and position of the MTDs include the presence of free gas, normal faulting in the slope sediments, and seafloor relief related to igneous activity. From MTDd to MTDb, slope failures are shown to have retrogressed upslope with a decreasing time interval between events. The events, dimensions, susceptible factors and formation processes of slope failures in the study area are demonstrated for the first time in the petroliferous basin of northern SCS. Their recognition is important for geo-hazard assessment (e.g. tsunami) in this area. Moreover, this study highlights that the lithostratigraphy of the slope succession, especially the coarse-grained sediments in the deepwater area, can be an important component for the occurrence of slope failures, and may be a key factor in slope stability on other continental margins too.